Consumption Volatility and Financial Openness - Claudia M. Buch; Serkan Yener (Kiel Institute for World Economics (IfW), 2005)
Economic theory predicts that the integration of financial markets lowers the volatility of consumption. In this paper, we study long-term trends in the consumption volatility of the G7 countries. Using different measures of financial openness, we find some evidence that greater financial openness has been associated with lower consumption volatility. However, volatility of consumption relative to output has not declined.
Keywords: F41; F36; 330; Consumption volatility; financial integration; G7 countries; Gesamtwirtschaftlicher Konsum; Volatilität; Kapitalmarktliberalisierung; Internationaler Finanzmarkt; Marktintegration; Schätzung; G-7-Staaten